What are the symptoms of varicose veins? Edinburgh vein study cross sectional population survey. Issue 7180 (6th February 1999) - Bradbury, Andrew; Evans, Christine; Allan, Paul; Lee, Amanda; Vaughan Ruckley, C; Fowkes, FGR
Abstract: Objective : To define the relations between age, sex, lower limb symptoms, and the presence of trunk varicose veins on clinical examination. Design : Cross sectional population study. Setting : 12 general practices with catchment areas geographically and socioeconomically distributed throughout Edinburgh. Participants : An age stratified random sample of 1566 people (699 men and 867 women) aged 18-64 selected from the computerised age-sex registers of participating practices. Main outcome measures : Self administered questionnaire on the presence of lower limb symptoms and physical examination to determine the presence and severity of varicose veins. Results : Women were significantly more likely than men to report lower limb symptoms such as heaviness or tension, swelling, aching, restless legs, cramps, and itching. The prevalence of symptoms tended to increase with age in both sexes. In men, only itching was significantly related to the presence and severity of trunk varices (linear test for trend, P=0.011). In women there was a significant relation between trunk varices and the symptoms of heaviness or tension (P 0.001), aching (P 0.001), and itching (P 0.005). However, the level of agreement between the presence of symptoms and trunk varices was too low to be of clinical value, especially in men. Conclusions : Even in the presence of trunk varices, most lower limb symptoms probably have a non-venous cause. Surgical extirpation of trunk varices is unlikely to ameliorate such symptoms in most patients.